Investigation by the Method of INNO-LiPA of Primary Resistance to Lamivudine in Patients with Chronic Hepatitis B Who Have Not Used Antiviral Therapy - Ozguler, M.; Akbulut, A.; Demirdag, K.; Ozden, M. (Univ West Indies Faculty Medical Sciences, 2016)
Aim: Two billion people around the world are exposed to the hepatitis B virus (HBV) and about 350 million are infected with chronic HBV. The infection can be acquired early (neonatal) and becomes chronic in 90%; this rate reduces to 30% between ages one and five years. There is a 25% risk of chronicity in adults. Nowadays, immunomodulatory and antiviral pegylated-interferons or oral antiviral agents are used in the treatment of chronic hepatitis B. Lamivudine is an effective oral antiviral agent which inhibits the replication of HVB by blocking reverse transcriptase enzyme. The study aims to detect the resistance of HBV to lamivudine in the community and evaluate the effectiveness and suitability of early treatment with lamivudine. Subjects and Methods: One hundred patients who presented to our Faculty of Medicine Hospital Infectious Diseases and Clinical Microbiology Department and had not received any antiviral treatment were recruited. The INNO-LiPA method was applied to investigate primary lamivudine resistance in patients. Results: Seventy-eight patients were HBeAg-negative and 22 patients were HBeAg-positive. A statistically significant correlation was found between HBeAg positivity, alanine aminotransferase (ALT) elevation and HBV DNA (p < 0.05). The rtM204V and L180M mutation motif was found in one patient with HBeAg positivity. Conclusions: Hepatitis B virus in our region is not a lamivudine-resistant strain and early treatment with lamivudine is an effective and convenient method.
Keywords: Chronic hepatitis B; INNO-LiPA; lamivudine; primary resistance